If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -28 = 22 + -1x Reorder the terms: -28 + -6x = 22 + -1x Solving -28 + -6x = 22 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -28 + -6x + x = 22 + -1x + x Combine like terms: -6x + x = -5x -28 + -5x = 22 + -1x + x Combine like terms: -1x + x = 0 -28 + -5x = 22 + 0 -28 + -5x = 22 Add '28' to each side of the equation. -28 + 28 + -5x = 22 + 28 Combine like terms: -28 + 28 = 0 0 + -5x = 22 + 28 -5x = 22 + 28 Combine like terms: 22 + 28 = 50 -5x = 50 Divide each side by '-5'. x = -10 Simplifying x = -10
| 12g+16=20g-40 | | x+5+2x=3x+5 | | x^2=(-3/8)x | | .75x+1000=6x | | R/5=18 | | -2.25t=-36 | | 8x=4(3+x) | | x^2=-3/8x | | 7+9t=10t | | 6x^7/2x^9 | | 2s+9=6s+15 | | -8m=-7m+8 | | 39s=312 | | -3.7=-22-1.5q | | 5z+9=4z | | -4=v | | 2x+5+x-3x+1=39 | | 3log(9x-2)=1 | | 1.95(6.2-3x)4.81=-18.46 | | F/15=-1 | | 0.75/36 | | 5x=4y+17 | | 3x+y=-41 | | -3x-7+4x+7= | | (x)=x^5-3x^4+12x^3-28x^2+27x-9 | | .75(4)+4.50= | | -76=w-73 | | x^2+5=x | | 3j=8+j | | 73+59= | | z/7=3 | | 7(9x+13)=406 |